Media Pembelajaran Biologi Berbasis Ecopreneurship - Fajar Adinugraha (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The objective of the research is to describe the form of the learning media which are created by the students. The research also to know entrepreneurship skill of students in the making of learning media based on ecopreneurship. The research method is descriptive research that is supported by quantitative data. The population is participants of Greenject 2017 competition, which requires 68 high school students in Jabodetabek or 34 teams. The sample is the finalist of education category (learning media) as many as 10 teams (20 students). Biology learning media can be made from used materials (garbage). The used materials being used are useless paper, useless cardboard, useless iron and zinc, scrap wood, plastic and useless electronic equipment. The learning media for biology lesson which is created by students are proven worthy of using as media of learning. As a matter of fact, some learning media are worthy of mass production. The entrepreneurship skills of students are in good category (40% excellent category and 60% good category). The production of learning media from the used materials can be used as a model of green entrepreneurship education or ecopreneurship.